The use of tDCS as a therapeutic option for tinnitus: a systematic review - Santos,Amanda dos Humildes Maia (2018)
Abstract Introduction: Due to the subjectivity of the tinnitus diagnosis and its diverse etiologies, establishing an effective treatment is complex. In this context, transcranial direct current stimulation, a noninvasive option, is available for most patients and has shown good results in the treatment of other symptoms such as chronic pain. Objective: To evaluate the therapeutic response of tinnitus to transcranial direct current stimulation. Methods: A systematic review of the literature was performed using the following descriptors: tinnitus, transcranial direct current stimulation and randomized clinical trial. The research was carried out in the MEDLINE/PUBMED, Lilacs, and Scielo databases. The inclusion criteria were: patients over 18 years of age with no associated comorbidities, who had a diagnosis established by a specialist or through the application of previously validated scales and criteria applied by a non-specialist physician. Results: A total of 4165 studies were found, and a total of six were selected after the inclusion criteria were applied, obtaining a sample of 602 patients. Based on the defined criteria, there was a positive response to transcranial direct current stimulation in 14.86% of the participants. Conclusion: Based on literature studied, there is no therapeutic response of tinnitus to transcranial direct current stimulation.